All Days 2011
DOI: 10.2118/140519-ms
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Decline Curve Estimation for Tight/Shale Reservoirs

Abstract: Low-permeability (tight) and shale (gas and oil) reservoirs have emerged as a significant source of energy in North America. Recent advances in technology, such as long horizontal lateral/multi-lateral drilling combined with hydraulic fracturing, and new surveillance techniques, have enabled commercial production from ultra-low permeability reservoirs, previously considered source or cap-rock, not reservoirs. Forecasting well production for reserves estimation, hydraulic fracture stimulation optimization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…In the preceding decade, significant advances have been made in the development of analytical methods for analyzing production data and long-term forecasting from multifractured horizontal wells in unconventional reservoirs (Medeiros et al 2008;Ozkan et al 2011;Bello and Wattenbarger 2008). As mentioned by Ambrose et al (2011), despite these advances, the empirical methods are still the most popular methods for forecasting multifractured horizontal wells. For the purpose of tight/shale-gas reservoirs, where transient flow can last for a long time, the classic Arps decline-curve approach (Arps 1945) is not applicable, simply because its application is limited to boundary-dominated flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preceding decade, significant advances have been made in the development of analytical methods for analyzing production data and long-term forecasting from multifractured horizontal wells in unconventional reservoirs (Medeiros et al 2008;Ozkan et al 2011;Bello and Wattenbarger 2008). As mentioned by Ambrose et al (2011), despite these advances, the empirical methods are still the most popular methods for forecasting multifractured horizontal wells. For the purpose of tight/shale-gas reservoirs, where transient flow can last for a long time, the classic Arps decline-curve approach (Arps 1945) is not applicable, simply because its application is limited to boundary-dominated flow.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have been applied to horizontal wells with multiple fractures in tight formations, but tend to yield nonunique forecasts because of the number of parameters in the equations (Ambrose et al 2011). For example, there are four parameters to be determined for the power-law and three for the stretched-exponential method.…”
Section: Introductionmentioning
confidence: 99%
“…Many operators tend to avoid numerical models in favor of these types of models due to their ease of construction and maintenance (Ambrose et al, 2011), as well as ease of use in history matching of production data, i.e. parameter estimation, and estimation of original gas in place.…”
Section: Shale-gas Reservoir Modelingmentioning
confidence: 99%
“…They used the concept proposed by Ambrose et al (2011) to divide a heterogeneous completion into different divisions with different durations of linear flow and then suggested that any of the hybrid methods can be applied to any of the divisions. For this purpose, a number  j is associated with each division which indicates the ratio of drainage area of that division to the total drainage area.…”
Section: Heterogeneous Completionmentioning
confidence: 99%
“…The fractures for both wells are identical and both wells have the same fracture spacing. Based on the concept of dividing the systems into different divisions as per Ambrose et al (2011) and Nobakht et al (2011b), the reservoir/completion geometry shown in Figure 1 is divided into three divisions as shown in Figure 2.…”
Section: Multi-well Analysismentioning
confidence: 99%